Activity of Succinate Dehydrogenase in Human Spermatozoa Stored under Hypothermia Conditions - Alekseyevskaya, E. I.; Kramar, M. I.; Chub, N. N.; Todorov, P. T.; Rodionova, V. L. (Problems of Cryobiology and Cryomedicine, 2002)
The authors investigated the effect of about zero temperatures and cytochrome C on the activity of succinate dehydrogenase (SDG) in human spermatozoa. It has been established that cytochrome C contributes to the increase of spermatozoa motility and activity of SDG by 30% at the rehabilitation stage after hypothermia and therefore can be used for the improvement of sperm quality when preparing it for insemination.